2004
DOI: 10.1016/j.neuron.2004.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of Morphological Diversity of Dendrites in Drosophila by the BTB-Zinc Finger Protein Abrupt

Abstract: Morphological diversity of dendrites contributes to specialized functions of individual neurons. In the present study, we examined the molecular basis that generates distinct morphological classes of Drosophila dendritic arborization (da) neurons. da neurons are classified into classes I to IV in order of increasing territory size and/or branching complexity. We found that Abrupt (Ab), a BTB-zinc finger protein, is expressed selectively in class I cells. Misexpression of ab in neurons of other classes directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 34 publications
3
124
1
Order By: Relevance
“…In da neurons, the expression level of the homeodomain transcription factor Cut correlates with dendritic complexity (Grueber et al 2003a), but Cut expression was not detectably altered in the PNS of PcG mutants (data not shown). Finally, misexpression of the transcription factor Abrupt in class IV neurons causes a significant reduction in dendritic complexity (Li et al 2004;Sugimura et al 2004), but Abrupt expression is not affected in the PNS of PcG mutants (data not shown). Therefore, PcG genes appear to specifically regulate the BX-C Hox genes in class IV neurons but have no detectable effects or interactions with nanos, pumilio, rac, cdc42, abrupt, or cut to regulate dendrite development in class IV neurons.…”
Section: Analysis Of Genetic Interactions Between Pcg Genes and Genesmentioning
confidence: 92%
“…In da neurons, the expression level of the homeodomain transcription factor Cut correlates with dendritic complexity (Grueber et al 2003a), but Cut expression was not detectably altered in the PNS of PcG mutants (data not shown). Finally, misexpression of the transcription factor Abrupt in class IV neurons causes a significant reduction in dendritic complexity (Li et al 2004;Sugimura et al 2004), but Abrupt expression is not affected in the PNS of PcG mutants (data not shown). Therefore, PcG genes appear to specifically regulate the BX-C Hox genes in class IV neurons but have no detectable effects or interactions with nanos, pumilio, rac, cdc42, abrupt, or cut to regulate dendrite development in class IV neurons.…”
Section: Analysis Of Genetic Interactions Between Pcg Genes and Genesmentioning
confidence: 92%
“…4,64 Sensory neuron dendrite patterning is defined by the combinatorial activities of a group of transcription factors, including the homeodomain factor Cut (homolog of Cux1 and 2), the BTB-domain factors Abrupt and Lola, the Kr€ uppellike factor Dar1, the Iroquois factor Mirror, the bHLH-PAS factor Spineless, the PRDM factor Hamlet, and the EBF factor Knot. 41,[68][69][70][71][72][73][74][75][76][77][78] These studies have demonstrated that individual transcription factors control specific aspects of dendrite cytoskeleton organization; for example, Cut and Lola were shown to regulate actin organization, 41,76,78 while Knot, Dar1, and Abrupt regulate microtubule organization. 20,41,77 A complex interacting network of microtubule regulatory events occurs within the differentiating neuron, 7 and consequently, a microtubule regulator that is an effector of a transcription factor need not be under the direct transcriptional control of that factor.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…In Drosophila class I neurons, Abrupt prevents branching to create the simple arbor morphology characteristic of this class. 20,74,75 Cnn was found to be a transcriptional target of Abrupt. Loss of Abrupt leads to Cnn downregulation and the decoupling of microtubule nucleation from Golgi outposts, thereby causing an increase in anterograde microtubule nucleation events and the de-repression of branching.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…Abrupt is a BTB-zinc finger protein of the Knot/Collier family of proteins that contributes to the transcriptional regulation of dendritic arborization in class I da neurons [26][27][28]. Specifically, Abrupt dose-dependently diminishes dendritic branching [27], thereby likely coordinating with Cut to establish the class I-specific lack of a dendritic arbor in post-mitotic neurons.…”
Section: Transcription Factor Involvement In Dendritic Plasticitymentioning
confidence: 99%